Thermoregulation of Girolando cows during summertime, in Pernambuco State, Brazil - doi: 10.4025/actascianimsci.v35i2.16591 - Ivalda de Albuquerque Lima; Marcilio de Azevedo; Christhiano Raphael de Albuquerque Borges; Marcelo de Andrade Ferreira; Adriana Guim; Gledson Luiz Pontes de Almeida (Acta Scientiarum. Animal Sciences, 2012)
This work was carried out to evaluate the physiological thermoregulation responses of Girolando-breed dairy cows kept in feedlot during summertime. A total of 15 animals were used, belonging to three genetic groups: 1/2, 5/8 and 3/4 Holstein-Gir (HG), with five cows from each genetic group, distributed in a completely randomized design, in subplots. The physiological parameters were sweat rate (SR), respiratory rate (RR), epidermis temperature (ET) and coat surface temperature (CST), and were evaluated once a week, during nine weeks, from December 2009 to February 2010, totaling 135 observations. Throughout the experimental period, climatic data were recorded using an automated weather station, and later used to calculate the different thermal comfort indexes: THI (temperature-humidity index), BGHI (black globe temperature and humidity index) and RTL (radiant thermal load). 1/2 HG animals showed the highest SR and lowest RR, ET and CST of all three genetic groups, while 3/4 HG cows had the lowest mean SR and highest ET and CST. 5/8 HG cows had intermediate values for SR, ET and CST. Mean RR values did not differ between 5/8 and 3/4 HG cows. It was concluded that animals from genetic groups 3/4 and 5/8 HG showed greater sensibility to heat stress than 1/2 HG cows.